Design and simulation of the accumulator for servomechanisms of launch vehicle. Issue 14 (23rd October 2020) - Zheng, Bo; Zhao, Chun; Liu, Xin; Zhao, Shoujun; Zhang, Xiaosha
Abstract : The accumulator is a crucial component of the hydraulic power for servomechanisms of the launch vehicle, which has a significant effect on the performance and the mass power. Traditional design methods are mostly based on empirical formulas, which do not meet the requirements of the fine design of aerospace products. The physical model, the mathematical model of the accumulator and joint simulation model of the energy and the control loop are established, and parameters satisfying the extreme flight operation profiles are obtained, including the discharge volume, charge volume and charge pressure. The flight data of third‐stage servomechanisms of the Long March 3 series Launch Vehicle were analysed, which is consistent with the simulation data, indicating that the accumulator has exerted the maximum capability in the extreme flight condition, and the maximum mass power has been realised.